2009
DOI: 10.1016/j.molcel.2009.05.029
|View full text |Cite
|
Sign up to set email alerts
|

A Quorum-Sensing Antagonist Targets Both Membrane-Bound and Cytoplasmic Receptors and Controls Bacterial Pathogenicity

Abstract: Summary Quorum sensing is a process of bacterial communication involving production and detection of secreted molecules called autoinducers. Gram-negative bacteria use acyl-homoserine lactone (AHL) autoinducers, which are detected by one of two receptor types. First, cytoplasmic LuxR-type receptors bind accumulated intracellular AHLs. AHL-LuxR complexes bind DNA and alter gene expression. Second, membrane-bound LuxN-type receptors bind accumulated extracellular AHLs. AHL-LuxN complexes relay information intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

9
200
2
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 193 publications
(212 citation statements)
references
References 38 publications
9
200
2
1
Order By: Relevance
“…In another example of cross-inhibition, a high-throughput chemical screen of approximately 35,000 compounds led to the identification of 15 small molecules that inhibited the LuxN/AI-1 QS circuit in V. harveyi (129). Despite the fact that these molecules were initially identified in a screen for inhibition of the membrane-bound sensor kinase LuxN, one of these molecules, 4606-4237 (Table 3), which carries a phenoxyl group at the terminus of the acyl chain and has a homocysteine thiolactone group in place of the homoserine lactone moiety, was later demonstrated to act as an antagonist of the cytoplasmic receptor CviR of C. violaceum (128). Thus, despite the differences in sequence and/or signal transduction mechanisms by AHL receptor proteins, the similarities of their ligand-binding pockets can be sufficient to allow for cross-inhibition by the same inhibitor compound.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
See 4 more Smart Citations
“…In another example of cross-inhibition, a high-throughput chemical screen of approximately 35,000 compounds led to the identification of 15 small molecules that inhibited the LuxN/AI-1 QS circuit in V. harveyi (129). Despite the fact that these molecules were initially identified in a screen for inhibition of the membrane-bound sensor kinase LuxN, one of these molecules, 4606-4237 (Table 3), which carries a phenoxyl group at the terminus of the acyl chain and has a homocysteine thiolactone group in place of the homoserine lactone moiety, was later demonstrated to act as an antagonist of the cytoplasmic receptor CviR of C. violaceum (128). Thus, despite the differences in sequence and/or signal transduction mechanisms by AHL receptor proteins, the similarities of their ligand-binding pockets can be sufficient to allow for cross-inhibition by the same inhibitor compound.…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
“…Interestingly, the mechanism by which analogues antagonize LuxR-type receptor activity also appears to be variable depending on the ligand and the receptor. Swem et al generated and tested various analogues of the previously identified CviR antagonist 4606-4237, leading to the identification of C10HSL, CTL, and CL as additional CviR antagonists (Table 3) (128). Studies using purified CviR protein complexed with these antagonists indicated that three of the antagonists function by preventing receptor association with target DNA, while C10HSL functions instead by preventing a productive interaction with RNA polymerase while having limited impact on DNA binding by CviR (128).…”
Section: Inhibition Of Signal Detection Synthetic Signal Analogues Anmentioning
confidence: 99%
See 3 more Smart Citations